PRE-SERVICE TEACHERS’ TEACHING PERFORMANCE IN TEACHING ENGLISH TO YOUNG LEARNERS: INSTRUMENTAL CASE STUDY APPROACH - Debora Chaterin Simanjuntak (Eltin Journal : Journal of English Language Teaching in Indonesia, 2018)
The ultimate purpose of conducting this study is to explore teaching performance of pre-service in teaching English to young learners. This is an instrumental case study, using explanatory approach which scrutinize a particular case to gain insight to an issue or theory by involving sources of information to provide in-depth study. Furthermore the findings of this research is expected to underpin realistic aims and current curricular innovation for teaching English to young learners (TEYL). The findings of this study are classified into four aspects: Teaching Aim, Teaching Reflection, Teaching Approach, and Teaching Challenges. Pre-service teachers understood their purpose in teaching English young learners. Throughout the classroom observations and interviews, it was found that pre-service teachers provided relatable tasks for young learners; they focused on course objective; they established good bond with young learners before implementing the lessons. Their challenges in Teaching are to establish parent-teacher relationship and to identify learners’ learning skills. This study is expected to contribute insights to English language teaching area about Pre-service Teachers’ Teaching Performance in Teaching English to Young Learners by immersing into the world of teaching English to Young learners.